Pengenalan Mikrokontroler dan Peluang Kerjanya kepada Siswa SMK Bina Profesi Pekanbaru - Syahrul Imardi; Lusiana Lusiana; Dian Wahyuni; Hamdani Hamdani; Fajar Arifandi; Junaidi Akbar (Jurnal Pendidikan Tambusai, 2022)
This activity is a Community Service (PKM) by Lecturers, this activity aims to introduce and explain the use of microcontroller technology such as Embedded systems, Smart Systems and / internet of Think as well as job opportunities and business opportunities at SMK Bina Profesi Pekanbaru. The introduction of microcontroller technology is important to answer students' curiosity about how to compete and contribute in the future in the application of smart technology. The data analysis technique used is content analysis, which examines the main information discussed in the reference, relates it to each topic discussed, then concept mapping in the form of a comparison of each developed data. Activities are carried out by providing knowledge and providing examples with microcontroller programming simulations. The results of this activity are expected to contribute to providing knowledge and understanding of schools, teachers, and students in the field of microcontrollers so they can see the direction of technological development and business and work opportunities in the industrial 4.0 era in the future.